A Psychoanalysis of Player Unknown's Battlegrounds (PUBG) in the Context of India 2020–2021 - Debnath, Achintya (CyberOrient, 2023)
This article is based on field surveys and interviews among mobile users. It provides a heuristic framework for understanding the dynamics of violent content, recent issues regarding banning PUBG (player unknown's battlegrounds) video games, and the complex characteristics of its perspectives. More precisely, it brings up an explanation and relation between violence and certain video games primarily focused on mobile user gamers who play PUBG (or Free Fire or both). Furthermore, this study throws light on the hot debate of banning PUBG in India in 2020–21 and the context of oversimplified assumptions behind its ban. The entire frame of this article is based on individual interviews of mobile users and their thoughts and experiences on the matter. For this purpose, fifty interviews have been conducted among gamers–players who play PUBG, Free Fire, or both. Furthermore, this research will contribute to the video game debate that has been going on regarding the relation between violence and games which started as early as the 1970s (Kowert and Quandt 2021).